A General Framework for Sustainability Assessment of Manufacturing Processes - Saad, Mohammed Hassoun (2018)
A Master of Science thesis in Mechanical Engineering by Mohammed Hassoun Saad entitled, “A General Framework for Sustainability Assessment of Manufacturing Processes”, submitted in November 2018. Thesis advisor is Dr. Basil Darras and thesis co-advisor is Dr. Mohammad Nazzal. Soft and hard copy available.